2018
DOI: 10.1001/jamaoncol.2018.0035
|View full text |Cite
|
Sign up to set email alerts
|

Association of High Body Mass Index and Hepatocellular Carcinoma in Patients With Chronic Hepatitis B Virus Infection

Abstract: Role of the Funder/Sponsor: The funder/sponsor had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 5 publications
2
21
0
1
Order By: Relevance
“…Among CHB patients with cirrhosis who exhibited viral suppression (including those with HDV or HIV co‐infection), BMI ≥ 30.0 kg/m 2 is also identified as an independent HCC risk factor (HR = 2.67; 95% CI: 1.04 to 6.84; P = .041) 40 . Interestingly, the correlation between BMI and HBV‐related HCC is higher in women compared with men ( P < .001), which may be partially explained by gender differences in the relationship between BMI and total body fat 41 …”
Section: Risk Factors For Hbv‐related Hccmentioning
confidence: 97%
See 1 more Smart Citation
“…Among CHB patients with cirrhosis who exhibited viral suppression (including those with HDV or HIV co‐infection), BMI ≥ 30.0 kg/m 2 is also identified as an independent HCC risk factor (HR = 2.67; 95% CI: 1.04 to 6.84; P = .041) 40 . Interestingly, the correlation between BMI and HBV‐related HCC is higher in women compared with men ( P < .001), which may be partially explained by gender differences in the relationship between BMI and total body fat 41 …”
Section: Risk Factors For Hbv‐related Hccmentioning
confidence: 97%
“…Over the last four decades, the prevalence of obesity has increased approximately seven‐fold 38 . Numerous clinical studies have revealed strong links between obesity and the development of HCC 39‐42 . Our team recently published a prospective cohort study in CHB patients with complete viral suppression, indicating that a high body mass index (BMI ≥25.0 kg/m 2 ) is an independent predictor for ALT elevation 39 .…”
Section: Risk Factors For Hbv‐related Hccmentioning
confidence: 99%
“…For example, a high body mass index (BMI) has been shown to worsen the disease outcomes of HBV carriers. In a large Korean population-based cohort study, a strong association was revealed between high BMI and a higher risk for HCC among patients with CHB infection [26] . Also, diabetes mellitus (DM) was shown to have a synergistic impact on the HBV disease course, as amply illustrated by a large metaanalysis, including almost 22,000 patients with CHB [27] .…”
Section: Risk Factors For Hcc In Hbv Patientsmentioning
confidence: 99%
“…These alterations may be associated with rapid progression of chronic liver disease. 5 While some studies have revealed an association between obesity and progression of cirrhosis, poor prognosis and hepatocellular carcinoma risk, 6,7 others have reported lower BMI to be associated with poor prognosis in patients with hepatocellular carcinoma 8 and shorter survival following hepatectomy for hepatocellular carcinoma. 9 A seven to 10 percent weight loss has been recommended by European associations to promote significant improvement in liver histology and enzymes in nonalcoholic fatty liver.…”
Section: Relationship Between Bmi and Clinical Outcomes In Cirrhosismentioning
confidence: 99%